Effects of core strength training combined with Tai Chi Chuan for the musculoskeletal system and cardiopulmonary function in older adults: A study protocol for a randomized controlled trial. Issue 35 (August 2018) - Jia, Xiaofei; Jiang, Cai; Tao, Jing; Li, Yinyan; Zhou, Yu; Chen, Li-dian
Abstract: Background: According to the national census, China has gradually become an aging society; moreover, aging has become an irreversible worldwide trend in the twenty-first century. Aging can lead to decreased physical function, mobility, cardiopulmonary function and quality of life (QOL). The feasibility and benefits of core strength training (CST) and Tai Chi Chuan (TCC) in older adults (including improving cardiovascular, musculoskeletal, and mental health outcomes) have been confirmed in previous studies. To date, these exercise programmes have not been systematically compared, and the potential benefits of their combined use have not been tested. The primary objective of thiss tudy protocol is to evaluate the effects of CST compared to those of TCC on the function of the musculoskeletal system and the cardiopulmonary system in older adults. The second objective is to test the effectiveness of combined physical training that incorporates CST and TCC. Methods: A randomized, single-blind, parallel-controlled trial will be conducted. Three hundred eighty-four participants who meet the eligibility criteria will be randomly allocated into a control group, a CST group, a TCC group, and a combined group in a 1:1:1:1 ratio. Participants in the CST group and the TCC group will respectively receive CST and TCC training at a frequency of 1 hour per day, 5 days per week, totally 12 weeks. Participants in the combined group will receive 30 minutes CST and 30 minutes TCC training per day, 5 days per week, totally 12 weeks. No specific exercises will be required of the participants in the control group. Both musculoskeletal and cardiopulmonary function outcomes, including bone density detection, balance and coordination ability, walking ability, pain visual analogue scale (VAS) score, fall risk assessment, activities of daily living, pulmonary function tests, color sonography and electrocardiogram, will be evaluated by blinded operators at baseline, 13 weeks and 25 weeks (follow-up period). Discussion: The results of this study protocol are expected to clarify the synergistic effect of CST and TCC training on musculoskeletal and cardiopulmonary function in older adults. Furthermore, these findings will confirm whether combined or exclusive CST and TCC training, is more effective at improving functional outcomes in the elderly. Trial registration: Chinese Clinical Trial Registry: ChiCTR-IOR-17010769. Registration date: March 3, 2017.